2004
DOI: 10.1037/1099-9809.10.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Person Factors Associated With Suicidal Behavior Among African American Women and Men.

Abstract: This study compared person risk factors among the following groups of low-income, African American adults in an urban, public hospital: (a) suicide attempters and nonattempters, (b) male and female attempters, and (c) all 4 groups (50 female attempters, 50 female nonattempters, 50 male attempters, and 50 male nonattempters). Participants completed psychological distress, aggression, substance use, cognitive processes, religiosity/spirituality, and ethnic identity measures. Compared with nonattempters, attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 70 publications
6
74
0
Order By: Relevance
“…Such impulsivity in suicide attempts might be understood as an attempt to control the experience of panic and use of the coping strategy of escape-avoidance. Previous studies [42,43] have reported that suicide attempters might exhibit escape-avoidance behavior as a coping strategy, which corresponds to our observations. Since fear of losing control or going crazy accounts for the unique variance in the relationship between PD and suicidal ideation, this is a potentially important symptom to consider when evaluating the genesis of actual suicide attempts.…”
Section: Discussionsupporting
confidence: 79%
“…Such impulsivity in suicide attempts might be understood as an attempt to control the experience of panic and use of the coping strategy of escape-avoidance. Previous studies [42,43] have reported that suicide attempters might exhibit escape-avoidance behavior as a coping strategy, which corresponds to our observations. Since fear of losing control or going crazy accounts for the unique variance in the relationship between PD and suicidal ideation, this is a potentially important symptom to consider when evaluating the genesis of actual suicide attempts.…”
Section: Discussionsupporting
confidence: 79%
“…These attitudes may reflect philosophical differences in worldview that potentially underlie African Americans' seeming "protection" from suicide via religiosity and religious and spiritual well-being (e.g., Kaslow et al, 2004;Walker, Utsey, Bolden, & Williams, 2005). Future studies should continue to determine mechanisms and dimensions by which religiosity buffers risks for suicide in persons of African descent.…”
Section: Discussionmentioning
confidence: 99%
“…The second study involved African American men and women aged 18-64 years (n=200). Cases included 50 men and 50 women who were seen by medical or psychiatric services within 24 hours after a suicide attempt, and controls included 50 men and 50 women with no history of suicidal behavior who were seeking medical care in an urgent care clinic within the same hospital (Compton et al, 2004;Kaslow et al, 2004;Kaslow et al, 2005). Exclusionary criteria for both studies are detailed extensively in prior publications Thompson et al, 2002;Compton et al, 2004;Kaslow et al, 2004;Kaslow et al, 2005).…”
Section: Participantsmentioning
confidence: 99%